BRIDGING THE NURSING CARE GAP: BUILDING QUALITY NURSING SERVICES FOR GAYS WITH HIV/AIDS THROUGH STANDARDIZATION, ENHANCEMENT OF NURSES' COMPETENCE, AND PATIENT PARTICIPATION - Silalahi, Malianti; Pangaribuan, Santa Maria; Permaida, Permaida; Hermawan, Stepanus Maman (Nursing Current: Jurnal Keperawatan, 2024)
Nursing care is a crucial aspect in addressing health issues, including Human Immunodeficiency Virus (HIV)/ Acquired Immunodeficiency Syndrome (AIDS), especially within the gay population. A lack of knowledge regarding nursing care for this population can hinder the reduction of HIV/AIDS cases. There is a need for HIV/AIDS nursing care standards that are not only comprehensive but also sensitive to the specific perceptions and needs of gay patients. Negative perceptions of nursing care can affect the quality of care and patient involvement in managing their health. Therefore, this study aims to explore these perceptions. This study employed a qualitative descriptive design to gain a deep understanding of the perceptions of gay patients with HIV/AIDS towards nursing care. Data was collected through in-depth interviews with 14 participants selected purposively. The interviews were designed to explore the participants' views, experiences, and expectations regarding the nursing services they received. The collected data was analyzed using thematic analysis, allowing the researchers to identify and categorize the main themes from the gathered information. Two main themes were identified during this study: The desired professional nursing services for gay individuals with HIV/AIDS and the limitations of nurses in involving gay clients with HIV/AIDS in the nursing care planning process. Consistent and standardized nursing care services, as well as enhancing nurses' skills and abilities through mentoring and training, are the expectations of gay individuals with HIV/AIDS towards professional nursing care. A heavy workload is a limitation faced by nurses in providing optimal nursing care to gay individuals with HIV/AIDS.